a SOSIALISASI LINGKUNGAN KAMPUS DAN MOTIVASI KEPADA CALON MAHASISWA DI JAKARTA BARAT: SOSIALISASI LINGKUNGAN KAMPUS DAN MOTIVASI KEPADA CALON MAHASISWA DI JAKARTA BARAT - Febrian, Wenny Desty Febrian; Solihin, Agung; Al Faruq Abdullah , Muhammad (Andhara, 2021)
Devotion has a target, namely prospective high school students in the West Jakarta area. The goal is that high school students in West Jakarta can make choices that will have a short/long term impact, both in the form of benefits and risks. Likewise, choosing a college is a decision that will have an impact on the future of high school students in West Jakarta. Choosing a major that is not in accordance with self-interest also has a psychological impact, namely decreased resistance to pressure, concentration and decreased fighting power. Moreover, if the lesson becomes more difficult, the problems will increase, it can cause the lecture to be threatened with stopping in the middle of the road. Self-motivation and enthusiasm for college must be instilled in every student in studying. Of course there will be a phase where you feel bored with routine, including the world of lectures. Usually the feeling of boredom in college that arises can be caused by many factors. As for what can be done to motivate high school students This is Try to Remember the Purpose of College, give Self Reward As a Form of Appreciation to yourself, remember both people old, occasionally look down or be grateful, don't like to procrastinate, finally find your own learning method. After doing this Community Service, it can be applied to high school students. Keywords: Socialization, Motivation